CHOICE OF PARADIGM IN ARBITRATION: ARBITRATOR’S AUTONOMY OR PARTIES’ AUTHORITY? - Roosdiono, Anangga W.; Taqwa, Muhamad Dzadit (Faculty of Law, Universitas Diponegoro, 2024)
The choice of paradigm in dispute resolution through arbitration raises a fundamental question: should the arbitral tribunal render its decision based on the law or ex aequo et bono? Most legal scholars affirm that the disputing parties have the full authority to dictate the tribunal's choice of paradigm in resolving disputes. This perspective, in Indonesia, is justified by two grounds: the Elucidation of Article 56(1) of Arbitration and Alternative Dispute Resolution Law, and the party autonomy principle in arbitration. Against this mainstream view, this paper repositions the role of arbitrators, emphasizing that they should possess autonomy -rather than being dictated to-when choosing the paradigm dispute resolution. This paper concludes that the choice of paradigm should rest within the authority of arbitrators.